Redescription of the pupa of Mallochohelea termophila (Diptera: Ceratopogonidae) - Maria Marcela Ronderos (Revista Mexicana de Biodiversidad)
The pupal exuviae of Mallochohelea termophila (Spinelli) is redescribed, photographed and illustrated mainly based on the type-series. Pupae of the type-series were collected with forceps from a thermal stream and were attached to rocks about 200 m from the spring head, and pupae from Uruguay with a deeper in lotic and lentic environments. They were reared to adults in the laboratory. This is the first detailed pupal description of a species of Mallochohelea Wirth, and the first record of this species from Uruguay. Similarities and differences with the pupae of NeobezziaWirth & Ratanaworabhan are provided.